Co-constructing knowledge with youth: what high-school aged mentors say and do to support their mentees' autonomy, belonging, and competence. Issue 2 (15th March 2023) - Dantzer, Benjamin; Perry, Nancy
ABSTRACT: Self-Determination Theory's (SDT) most recent 'mini-theory, ' Relationships Motivation Theory (RMT) focuses on the essential ingredients of high-quality relationships (i.e. feelings of autonomy, belonging, and competence). This study explores the applicability of RMT to cross-age peer mentoring. Of particular interest was whether the RMT framework could help high-school mentors develop positive relationships with their elementary-aged mentees. The specific language and strategies mentors used to support feelings of autonomy, belonging, and competence was also of interest, as this level of detail has not been captured in previous research. High-school mentors were invited to learn about RMT during skill-building sessions. They were then asked to apply the language and skills they co-developed during mentoring sessions. Data included audio recordings of dyadic interactions, weekly mentoring logs, and interviews. Descriptive, Provisional, and In-Vivo coding were used to analyze data. Qualitative coding indicated high-school mentors were capable of co-constructing language and practices to support mentees' feelings of autonomy, belonging, and competence. Findings also indicated that mentors successfully applied this knowledge to mentoring sessions. Weekly mentoring logs indicated skill-building sessions helped mentors develop positive relationships with their mentees. The results of this study begin to suggest that RMT can help inform the cross-age peer mentoring process.